2018
DOI: 10.3390/ijerph15112375
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to Climate-Induced Disasters and Its Overall Relationship to Well-Being in Southern Africa: A Mixed-Methods Systematic Review

Abstract: The available literature suggests that natural disasters, especially droughts and floods, were occurring in southern Africa in the early 1900s. However, their frequency and intensity increased during the 1980s. The aim of this systematic review was to assess the relationship between resilience to droughts and people’s well-being in southern Africa. A combination of keywords was used to search the following 13 electronic bibliographic databases: Africa Journal Online (AJOL), MEDLINE, Academic Search Complete, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…Regionally, there has been limited success in efforts to benchmark resilience. A recent systematic review of resilience in southern Africa noted the lack of a contextually and culturally appropriate resilience framework [58]. The review further observed that most of the relevant studies did not exhibit the rigour necessary to qualify as resilience research.…”
Section: Introductionmentioning
confidence: 99%
“…Regionally, there has been limited success in efforts to benchmark resilience. A recent systematic review of resilience in southern Africa noted the lack of a contextually and culturally appropriate resilience framework [58]. The review further observed that most of the relevant studies did not exhibit the rigour necessary to qualify as resilience research.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our definition of policy, we included a broad range of policy documents (see Table 2). e included policy documents were published after 1 January 1980, when drought frequency and intensity increased alongside emergency drought appeals for 4 Discrete Dynamics in Nature and Society international assistance [6,25]. Table 2 presents our broad inclusion and exclusion criteria.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Climate-induced hazards have continuously eroded development gains and livelihoods, disrupted societal routines, and affected human health and wellbeing [2,3]. e last three decades have seen significant increases in climate-induced hazards such as drought occurrences which have become longer and severely exacerbated poor agricultural outputs, livestock losses, and poor health and wellbeing [3][4][5][6]. e governments in the region have responded with various policy instruments to address the threat of recurrent drought.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of emergency management, hazard‐specific expertise is exceptional knowledge and understanding of the behavioural characteristics and associated risks that a specific agent has the potential to cause (EMPS, 2019; Scheer et al, 2014). Multi‐agency responses requiring increased inter‐operability, the greater frequency of climate‐induced disasters (Kamara, Akombi, Agho, & Renzaho, 2018), inter‐jurisdictional deployments both nationally and internationally (Amat Camacho, Karki, Subedi, & Von Schreeb, 2019; Bartolucci, Walter, & Redmond, 2019) and the expectation that commanders manage non‐hazard‐specific incidents (EMPS, 2019) all point towards this issue becoming more, rather than less of a challenge.…”
Section: Introductionmentioning
confidence: 99%